A discursive analysis of literary and cinematographic mechanisms in the stories of Gonzalo Suárez - Hernández Ruiz, Javier (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Gonzalo Suárez is one of the few Spanish creative artists to have developed his work simultaneously in cinema and literature.The focus of analysis here is on how he organizes the narrative discourse of his stories in each medium, with special reference to narrative structure, aspect and voice. It is only by proceeding thus that a point of departure can be established for a study of the mechanisms involved in working between the two media; a transference which is far removed from the more traditional models of adaptation and which opts for a much more creative relation in which it is not the mimetic mode that dominates but rather the attempt to translate the different discursive mechanisms into the specific medium of cinema or literature.
Keywords: Gonzalo Suárez; cine; short stories; narrative